The Implementation of Traditional Jaranan Dance Activities to Enhance Gross Motor Development in Children at TK Kartini Sungai Rumbai - Trisnawati, Ernita; Siska, Widia; Andre, Lesis; Afriwes, Afriwes (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The background of this study is the low gross motor development of early childhood at Kartini Kindergarten, Sungai Rumbai. The purpose of this study is to determine the implementation of traditional Jaranan dance activities, children's gross motor development through traditional Jaranan dance activities, and the obstacles faced by teachers in implementing traditional Jaranan dance activities at Kartini Kindergarten, Sungai Rumbai.This study is a qualitative descriptive study. The subjects were two classroom teachers and 17 students. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, data display, and conclusions (verification). Data validity techniques included data triangulation.The results of the research on the implementation of traditional Jaranan dance activities at Kartini Kindergarten, Sungai Rumbai, consisted of preparing materials or media, arranging rows of children, giving examples of movements to children, demonstrating imitation of dance movements and conducting evaluations. The gross motor development of children at Kartini Kindergarten, Sungai Rumbai, was increasing in accordance with expectations (BSH) from 10 children who received a value of developing according to expectations (BSH) with a percentage of 59% and 7 children received a value of developing very well (BSB) with a percentage of 41%. In the balance indicator, walking in holding the horse's head and whip in the hand simultaneously while swinging, forward and backward increased by 76%. In the flexibility indicator, swinging the Jaranan head to the right and left increased by 88%. In the coordinated indicator, jumping forward and backward while moving the Jaranan increased by 71%. In the agility indicator when moving places while lifting one leg and lifting the whip with one hand increased by 88%. In the skilled indicator, the body walked to the right and left side while moving or shaking the hips increased by 76%. Research findings on the obstacles encountered in implementing the traditional Jaranan dance at Kartini Kindergarten, Sungai Rumbai, include limited space, children's lack of movement skills, a lack of teaching staff, inadequate infrastructure, and children's tendency to make noise and talk.